2018
DOI: 10.1038/s41388-018-0190-7
|View full text |Cite
|
Sign up to set email alerts
|

A RAS-CaMKKβ-AMPKα2 pathway promotes senescence by licensing post-translational activation of C/EBPβ through a novel 3′UTR mechanism

Abstract: Oncogene-induced senescence (OIS) is an intrinsic tumor suppression mechanism that requires the p53 and RB pathways and post-translational activation of C/EBPβ through the RAS-ERK cascade. We previously reported that in transformed/proliferating cells, C/EBPβ activation is inhibited by G/U-rich elements (GREs) in its 3′UTR. This mechanism, termed “3′UTR regulation of protein activity” (UPA), maintains C/EBPβ in a low-activity state in tumor cells and thus facilitates senescence bypass. Here we show that C/EBPβ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 63 publications
(89 reference statements)
1
15
0
Order By: Relevance
“…RNA FISH labeling showed exclusion of Cebpb mRNAs from the perinuclear region (Fig. S2A), as observed previously (Basu et al, 2018a). Interestingly, UPF1 was restricted to the perinuclear area that was largely devoid of Cebpb FISH signals.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…RNA FISH labeling showed exclusion of Cebpb mRNAs from the perinuclear region (Fig. S2A), as observed previously (Basu et al, 2018a). Interestingly, UPF1 was restricted to the perinuclear area that was largely devoid of Cebpb FISH signals.…”
Section: Resultssupporting
confidence: 88%
“…To begin to address whether the GRE Δ/Δ genotype confers resistance to RAS-induced transformation, we crossed the mutant strain to mice lacking the p19 Arf tumor suppressor and prepared MEFs of four genotypes: WT , GRE Δ/Δ , p19 Arf−/− , and p19 Arf−/− ;GRE Δ/Δ . As C/EBPβ UPA is abrogated in RIS cells but not in RAS-transformed tumor cells (Basu et al, 2018a) and p19 Arf deficiency circumvents senescence to facilitate neoplastic transformation, we reasoned that ΔGRE phenotypes may be more apparent in cells lacking p19 Arf . RAS-induced phosphorylation on Ser222 was enhanced more ∼1.7-fold in p19 Arf−/− ;GRE Δ/Δ MEFs compared to p19 Arf−/− cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the intracellular site of the C/EBPβ translation is critical for RAS-induced activation via effector kinases such as ERK. Interestingly, 3′UTR inhibition and C/EBPβ mRNA compartmentalization are not observed in primary mouse and human fibroblasts [ 64 ].…”
Section: C/ebps and Cancermentioning
confidence: 99%
“…Interestingly, cumulative studies have shown that HuR promotes cell senescence, which is closely related to tumors, by increasing reactive oxygen species (ROS) by enhancing the mitochondrial localization of the telomeric protein TIN2 and increasing Foxp3 expression, activating oncogene-induced senescence via the Ca ++ -CaMKK β -AMPK α 2-HuR pathway, etc. [ 27 29 ]. Therefore, studying the functional properties of HuR plays a crucial role in the future prevention and treatment of tumors.…”
Section: The Role Of Hur In Affecting the Biological Characteristimentioning
confidence: 99%